Multicultural-Based Communication Strategies in Language Teaching - Rifa'i, Arif Ma'mun; Sadiran, Sadiran; Muasomah, Luluk (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study explores the role of multicultural communication strategies in language teaching, emphasizing the importance of culturally responsive pedagogy in addressing the diverse backgrounds of learners. Drawing on a qualitative library research method, this work synthesizes existing literature to construct a conceptual framework that highlights the integration of cultural identity, responsive interaction, and inclusive content in language education. This study uses a qualitative library research method to examine multicultural communication strategies in language teaching. Data were gathered from credible academic sources through systematic literature searches using relevant keywords. The analysis applied qualitative content analysis to identify themes related to cultural identity integration, responsive teacher-learner interactions, and inclusive curricula, resulting in a conceptual framework for fostering culturally responsive pedagogy in diverse classrooms. Findings indicate that effective communication in multicultural classrooms extends beyond linguistic instruction to include intercultural competence and sensitivity to students’ cultural norms, values, and communicative styles. The study identifies both the benefits and challenges of implementing such strategies, noting that while they enhance student engagement and learning outcomes, their application is often hindered by a lack of institutional support, teacher training, and adaptable curricula—particularly in contexts like Indonesia. This research advocates for comprehensive teacher development, curriculum reform, and reflective practices that empower educators to bridge linguistic and cultural divides. Ultimately, the study underscores the need for pedagogical models that foster inclusive, equitable, and culturally affirming learning environments in 21st-century language classrooms.